Sintesis Nanokitosan Dengan Metode Gelasi Ionik Menggunakan Pelarut Asam Formiat Dengan Variasi Rasio Volume Kitosan Dan Natrium Tripolifosfat - Aulia Permatasari; Ahmad Fadli; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Nanochitosan is a physical modification of chitosan by reducing the size of chitosan to nano size. The purpose of this research was to determine the effect of variations in volume ratio between chitosan solution and tripolyphosphate solution and to determine the characteristic of nanochitosan with Particle Size Analyzer (PSA) analysis methods. The first step for making nanochitosan is to make a 1% formic acid solution and 0.1% trypolyphosphate solution. After that, make 0.3% chitosan solutions and then stir it using magnetic stirrer. After 15 minutes, trypolyphosphate solution at a volume ratio between chitosan and trypoliphosphate each 3:1 and 7:1 are added slowly to the chitosan solution. Stirring continues for up to 1 hour with a stirring speed of 1200 rpm. The last one is the characterization of nanochitosan. Chitosan from dried shrimp industrial waste has a degree of deacetylation that matches the chitosan quality standard, which is 76%. The particle size from this research were 2639.5 nm and 2882.0 nm. From this research, the particle size and index polydispersity value were increased when the ratio between chitosan solution and tryppoliphosphate increased. Keywords: formic acid, deacetylation degree, ionic gelation, nanocitosan, trypolyphosphate